Integrasi Ilmu Farmasi dan Nilai-Nilai Syariah dalam Perspektif Islam - Imam Samodra; Mashur (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The integration between pharmaceutical sciences and sharia values has become increasingly urgent amidst the rapid development of the global pharmaceutical industry and the growing awareness of Muslim communities regarding the halal status of health products. This study aims to construct a holistic integration model that unifies epistemological aspects, production operational standards, pharmaceutical care services, and regulatory policies. The method employed is library research using content analysis and synthesis approaches on Islamic literature, jurisprudence, maqasid al-shariah, as well as pharmaceutical scientific literature and halal regulations. The results indicate that integration encompasses three main domains: production operational standards (critical points on gelatin, alcohol, enzymes, and cross-contamination), spiritually responsive pharmaceutical care (screening, counseling, therapy modification, referral, and spiritual accompaniment), and cross-institutional regulatory harmonization. The novelty of this research lies in its simultaneous and applicable integrative model, differing from previous partial studies. The conclusion recommends phased solutions ranging from pharmacist training, curriculum reinforcement, industrial incentives, to halal pharmacist professional certification. Further empirical research is essential to test the proposed model